Experimental and Numerical Investigation of a Refrigerator Unit for a Refrigerated Vehicle - Wang Zhenhuan; Choi Younsung; Wang Shanshan (Zhileng xuebao)
To examine the influence of different parameters of a 10 kW refrigeration unit on the performance of a refrigerated vehicle, the capacity, coefficient of performance (COP), and pressure performance of the circulation system of a refrigeration unit were tested using experimental and simulation methods. Additionally, changes were made to the refrigerant charge, degree of superheating, and refrigerant type to conduct experimental and simulation studies. The results showed that the capacity and COP of the refrigeration unit exhibited different trends with changes in the refrigerant charge and superheat. The cooling capacity and COP errors between simulation and experiment were 6.4% and 8.5%, respectively, and the error of all results was within 10%. It was confirmed that the performance variation in the refrigeration unit was more sensitive to the variation in the degree of superheating than to the refrigerant charge. The best capacity and COP were achieved when the degree of superheat was 4 ℃ and the refrigerant charge was 7.4 kg. Furthermore, through numerical simulation, it was determined that the COP performance of the refrigerant R449A, used in the refrigeration cycle system, was approximately 4% higher than that of R404A. It was confirmed that the refrigerant R449A can be used instead of R404A.